Local response to global uncertainty: Insights from experimental economics in small-scale fisheries. (January 2018) - Finkbeiner, E.M.; Micheli, F.; Saenz-Arroyo, A.; Vazquez-Vera, L.; Perafan, C.A.; Cárdenas, J.C.
Highlights: Resource users can exhibit stewardship behavior in the face of uncertainty. Past experience, social capital and strong institutions are related to this behavior. Local action is important for mitigating and buffering effects of global change. Abstract: Global change has systematically increased uncertainty for people balancing short-term needs with long-term resource sustainability. Here, we aim to understand how uncertainty drives changes in human behavior and the underlying mechanisms mediating use of behavioral strategies. We utilize a novel behavioral approach – dynamic common-pool resource economic experiments in the field – and apply it to small-scale fisheries as a system that is particularly vulnerable to global change. Contrary to previous research, we find that when faced with higher uncertainty, resource users are choosing to reduce harvest to compensate for potential future declines. Correlates of this behavior include the capacity for social learning, previous exposure to uncertainty, and strong local institutions. These findings have important implications for any local system facing increased uncertainty from global change. Given adequate access to resources and rights, local communities can be active agents of change, capable of addressing and mitigating impacts of processes generated by higher scales.